2008
DOI: 10.1007/s00432-008-0385-3
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of RB1 gene in embryonal and alveolar rhabdomyosarcoma: special reference to utility of pRB immunoreactivity in differential diagnosis of rhabdomyosarcoma subtype

Abstract: Our results support the assertion that tumorigenesis of RMS may be associated with RB1 alteration especially in ERMS, as previously reported for osteosarcoma. As for the RB pathway, each subtype of RMS may have a different tumorigenesis. In addition, immunohistochemical pRB LI may have the potential to be a useful ancillary tool in the differential diagnosis of RMS subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
(34 reference statements)
0
31
0
Order By: Relevance
“…Consistent with a role in osteosarcoma development, mouse models have shown that loss of Rb can potentiate the development of osteosarcomas in the context of mutant p53 (Berman et al, 2008;Walkley et al, 2008). However, despite the clear role of Rb in osteosarcoma development, attempts to identify a role for Rb in STSs have been met with conflicting reports (Cance et al, 1990;Karpeh et al, 1995;Dei Tos et al, 1996;Kohashi et al, 2008). Attempts to generate STSs in transgenic animals have not demonstrated a causative role for Rb in their development.…”
Section: Lessons From the Earliest Models Of Stsmentioning
confidence: 99%
“…Consistent with a role in osteosarcoma development, mouse models have shown that loss of Rb can potentiate the development of osteosarcomas in the context of mutant p53 (Berman et al, 2008;Walkley et al, 2008). However, despite the clear role of Rb in osteosarcoma development, attempts to identify a role for Rb in STSs have been met with conflicting reports (Cance et al, 1990;Karpeh et al, 1995;Dei Tos et al, 1996;Kohashi et al, 2008). Attempts to generate STSs in transgenic animals have not demonstrated a causative role for Rb in their development.…”
Section: Lessons From the Earliest Models Of Stsmentioning
confidence: 99%
“…Alterations in CDKN2A and its downstream effectors Retinoblastoma 1 (Rb1) and Tp53 have been noted in human STS (3,16,17), and one study reported reduced or absent expression of p16 INK4A and/or p14 ARF in human RMS (18). Together, these data implicate both oncogenic Kras and dysregulated p16p19 as clinically relevant, sarcoma-associated lesions.…”
mentioning
confidence: 94%
“…16 The genomic landscape causative of ERMS is characterized by a number of genetic lesions and/or somatic mutations that deliberately sustain the activity of different receptors, such as IGF1R, FGFR4 and Patched, [17][18][19][20][21] and related downstream pathways (i.e., RAS/ERK, PI3K/AKT and Sonic Hedgehog signaling). 11,22 In addition, defects in tumor suppressors (i.e., p53), 23 cell cycle regulatory genes (i.e., N-Myc, Rb1) 21,24 and structural proteins involved in muscular integrity (i.e., dystrophin, alpha-sarcoglycan and dysferlin) have been reported. [25][26][27][28][29][30] Conversely, ARMS is dominated by the presence of specific chromosomal translocations leading to expression of the fused Pax3-Foxo1 and Pax7-Foxo1 factors, that driving in a cell cycle manner the transcription of several genes normally restricted to the embryonal development favor tumor initiation in some muscle precursors.…”
mentioning
confidence: 99%